EFFECT OF DIFFERENT LEVEL OF PROTEIN ON GROWTH PERFORMANCE, SURVIVAL RATE, DIGESTIVE ENZYME, AND BODY PROTEIN COMPOSITION OF JUVENILE BESENG-BESENG FISH (Marosatherina ladigesi) - Jayadi Jayadi; Amrah Husma; Nursyahran Nursyahran (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2020)
Marosatherina ladigesi’s original habitat is in the freshwater of South Sulawesi as endemic fish in the wallacea zone Indonesia, with a local name called beseng-beseng fish. M.ladigesi was already in the category of at threat of extinction.The purpose of this study was to investigate the effect of different protein levels on survival rate, growth performance, body protein composition and enzyme activity of protease, lipase and amylase of beseng-beseng fish. The research method was using Completely Randomized Design with three treatments and three replications. Treatment of the study: protein content of feed A: 40%, B: 50% and C: 60%. Fish maintenance takes 90 days. The results showed that protein content had a significant effect (P<0,05) on absolute body growth, specific growt rate, survival rate, body protein composition and protease enzyme activity of juvenile beseng-beseng fish. The best growth performance is obtained at 50% and 60% protein content, while the survival and body protein composition and the best protease enzyme activity at 60% protein content.